The neighbor from outer space - George, Maureen; DiVito, Anna.; Copyright Paperback Collection (Library of Congress) (New York : Scholastic Inc., 1992)
When Katie, Chrissy, Maddie and Brian accidentally discover that their neighbor, Mr. Dugan, is an alien from outer space, their quiet summer suddenly becomes crazy.
"A Little Apple paperback."
Keywords: Unidentified flying objects -- Fiction; Children's stories; Science fiction